Analisis tekno ekonomi sistem hidrogen hijau dengan model matlab simulink di Lombok Indonesia - Parman, Parman; Hendrasakti, Jooned; Juangsa, Firman Bagja (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
This research conducts a techno-economic analysis of a green hydrogen system in Lombok, Indonesia, using a MATLAB Simulink-based simulation model. The primary objective of this study is to evaluate the long-term economic feasibility of a green hydrogen project through the analysis of key financial parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), and the break-even point. The model simulation results show that the production output of green hydrogen is 121,391 kg, and the project generates a Net Present Value (NPV) of $1,205,031.1 over a 25-year operational period. The Internal Rate of Return (IRR) of the project reaches 11.9%, indicating that the project has a promising profit potential. Additionally, the break-even point is achieved in the 8th year, meaning that the initial investment can be recouped by that time. These findings provide an initial overview of the economic prospects of green hydrogen development in Lombok and demonstrate the potential of green energy in supporting the energy transition in Indonesia. This study also offers guidance for policymakers and investors in making strategic decisions related to investments in renewable energy technology.